“Diabetic holiday foot syndrome”: Home and away - Beshyah, Salem (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Diabetic foot ulceration is a serious complication of diabetes mellitus worldwide. It is the most common cause of hospitalization in diabetic patients and is the most frequent cause of nontraumatic amputations. Furthermore, diabetic foot disease can impair patients' quality of life and affect social participation and livelihood. People with diabetes have a higher risk of foot ulceration during holidays, especially those taken in hot countries for various causes. These causative factors may also coexist at home. In this clinical vignette, two case histories, several photographic illustrations, and a focused review of the relevant literature are presented with the view of alerting practicing clinicians to such encounters.
Keywords: Burns; diabetic foot; holiday; neuropathy; wound healing